2016
DOI: 10.1002/phar.1742
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐Utility Analysis of Infliximab with Standard Care versus Standard Care Alone for Induction and Maintenance Treatment of Patients with Ulcerative Colitis in Poland

Abstract: Treatment with infliximab/standard care instead of standard care alone resulted in additional QALYs but also additional costs. The incremental cost per QALY gained of infliximab/standard care compared with standard care alone exceeded the willingness-to-pay threshold in Poland (equivalent to ~$33,400).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The results of the conducted analyses for biological treatment in Canada were not consistent – one analysis [26] showed that infliximab is a cost-effective treatment option compared with standard care and one [27] proved that anti-TNF-α therapies are not cost-effective compared with standard care. Conclusions for all three economic analyses, conducted for three different biologicals used in Poland, are consistent – infliximab, adalimumab, and golimumab turned out not to be cost-effective compared with standard care alone [2123]. …”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The results of the conducted analyses for biological treatment in Canada were not consistent – one analysis [26] showed that infliximab is a cost-effective treatment option compared with standard care and one [27] proved that anti-TNF-α therapies are not cost-effective compared with standard care. Conclusions for all three economic analyses, conducted for three different biologicals used in Poland, are consistent – infliximab, adalimumab, and golimumab turned out not to be cost-effective compared with standard care alone [2123]. …”
Section: Discussionmentioning
confidence: 94%
“…QALY was the endpoint of eight analyses [18, 19, 2123, 2527], remission and response was used in one study [24], and mucosal healing in another one [20]. The most commonly assessed biological agent was infliximab – eight studies [1820, 2327].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations